Practices of Supportive Church Children’s Ministries: An Exploratory Multilevel Investigation of Church of the Nazarene Congregations in the United States - Crosby, Robert G. (Review of religious research, 2021)
Religious communities have been identified as an important source of social support for children. Although church children’s ministries (i.e., church programs where children receive religious education separate from their parents) have been suggested as a potential avenue for the transmission of social support, the specific children’s ministry practices that promote social support have not been established empirically.The purpose of the present study was to determine whether contemplative-reflective practices, structured playtime, and unstructured playtime predict between-church differences in children’s church-based social support (i.e., received support, perceived support from peers, perceived support from adults) controlling for children’s individual characteristics and children’s ministry size.